2004
DOI: 10.1186/1471-2180-4-16
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of 16S rRNA genes amplified from normal and disturbed vaginal microflora suggests a strong association between Atopobium vaginae, Gardnerella vaginalis and bacterial vaginosis

Abstract: Background: The pathogenesis of bacterial vaginosis remains largely elusive, although some microorganisms, including Gardnerella vaginalis, are suspected of playing a role in the etiology of this disorder. Recently culture-independent analysis of microbial ecosystems has proven its efficacy in characterizing the diversity of bacterial populations. Here, we report on the results obtained by combining culture and PCR-based methods to characterize the normal and disturbed vaginal microflora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
118
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 304 publications
(131 citation statements)
references
References 44 publications
10
118
2
1
Order By: Relevance
“…We found 4 of 20 subjects with a significant number of Peptostreptococcus reads and another 3 subjects with a few reads of Peptostreptococcus. Atopobium was found in two of eight subjects by Verhelst et al (22) and was the only microbe in one of five subjects by Zhou et al (23). Four of our 20 subjects had a small number of Atopobium reads, subjects 03 (3 reads), 05 (41 reads), 09 (53 reads), and 43 (74 reads; Tables 9, 11, 15, and 23, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found 4 of 20 subjects with a significant number of Peptostreptococcus reads and another 3 subjects with a few reads of Peptostreptococcus. Atopobium was found in two of eight subjects by Verhelst et al (22) and was the only microbe in one of five subjects by Zhou et al (23). Four of our 20 subjects had a small number of Atopobium reads, subjects 03 (3 reads), 05 (41 reads), 09 (53 reads), and 43 (74 reads; Tables 9, 11, 15, and 23, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…As a direct consequence of our deep sequencing, we found an additional four subjects with a significant number of Streptococcus reads as well as three subjects with a few reads of Streptococcus. Verhelst et al (22) found no subjects with Streptococcus but one of eight subjects with Peptostreptococcus. We found 4 of 20 subjects with a significant number of Peptostreptococcus reads and another 3 subjects with a few reads of Peptostreptococcus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations